1988
DOI: 10.2466/pms.1988.67.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Rorschach Indices for Discriminating between Two Schizophrenic Syndromes

Abstract: Thinking disturbance and disorder of affects may be different in two subtypes of schizophrenia, the "florid" and the "withdrawal" syndromes. In Exner's approach to the Rorschach system, the diagnostic indicators of disordered thinking may point out large differences not only between schizophrenic and control subjects but also between different types of schizophrenics. The Rorschach protocols of 45 subjects (15 "florid" schizophrenics, 15 "withdrawn" schizophrenics, and 15 controls of the same age and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The patients showed serious processing and mediational problems (Zd, Lambda, X-%, X+%) that contribute to difficulties in adjustment. The high amount of mediational problems found in the patients of this study confirm, as expected, the well-established results of earlier studies of patients with schizophrenia spectrum disorders (Archer & Gordon, 1988;Exner, 1986Exner, , 1991Di Nuovo et al, 1988;Hilsenroth et al, 1998;Mason et al, 1985).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patients showed serious processing and mediational problems (Zd, Lambda, X-%, X+%) that contribute to difficulties in adjustment. The high amount of mediational problems found in the patients of this study confirm, as expected, the well-established results of earlier studies of patients with schizophrenia spectrum disorders (Archer & Gordon, 1988;Exner, 1986Exner, , 1991Di Nuovo et al, 1988;Hilsenroth et al, 1998;Mason et al, 1985).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of coping style, nearly half of the patients in this study showed an ambitent coping style, one third being extratensives and one fifth introversives. These results are in line with the results of a study by Di Nuovo et al (1988), but are in contrast to the results of Exner (1986Exner ( , 1991.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It can be argued that this had an impact on the results as the patients were no longer openly psychotic, i.e., their hallucinatory and/or delusional behavior had ceased. The tendency within studies relating to the SCZI seems to have been that administration takes place within the first week of admission for treatment (Archer & Gordon, 1988; Di Nuovo, Laicardi, & Tobino, 1988; Edell, 1987; Hilsenroth et al, 1998; Mason et al, 1985). Recent research, however, suggests that when the Rorschach is given to patients who are in an acute psychotic condition, the results may be quite misleading.…”
Section: Discussionmentioning
confidence: 99%
“…M has also been associated with sensory deprivation (Bendick & Klopfer, 1964), electromyography-based muscle potentials (Steele & Kahn, 1969), ability to discriminate florid and withdrawn schizophrenics from healthy subjects (Di Nuovo, Laicardi, & Tobino, 1988), and symptom improvement after psychotherapy (Exner & Andronikof-Sanglade, 1992;Weiner & Exner, 1991).…”
Section: Human Movement In the Rorschach Testmentioning
confidence: 99%